Peran Orangtua dalam Memotivasi Belajar Anak di Desa Bumirejo Kecamatan Selat Penuguan Kabupaten Banyuasin - Vina Muridyanti; Risma Anita Puriani; Alrefi Alrefi (Scidacplus, 2023)
The purpose of this study was to determine the role of parents in motivating children's learning in Bumirejo Village, Penuguan Strait District, Banyuasin Regency. The subjects of this study were 6 parents who had children and were currently studying at senior high school. The method used in this research is descriptive qualitative by collecting data through direct interviews with 6 respondents from Bumirejo Village. The results of the study show that parents' sense of awareness to improve or motivate their children to learn is sufficient even though it is only limited to giving attention and financing. Parents of children in Bumirejo Village are more likely to state that financial needs are more important for further education, this is due to family conditions and parents' knowledge that they do not understand the importance of motivating children's learning, and parents also have a different mindset so they assume that their children are already fully grown and independent so that they do not need guidance or supervision from their parents.